Differential seedling establishment of woody plants along a tree density gradient in Neotropical savannas - Salazar, Ana (2012)
Seedling dynamics are crucial for understanding spatial plant distribution patterns, yet little is known about seedling establishment in Neotropical savannas because empirical studies at the community level are scarce. Over 2 years, we studied the recruitment and survival of an initial seedling assemblage and three cohorts of recruits of woody plants within 216 plots of 1 m 2 located along a tree density gradient in the savannas of central Brazil. These savannas differ in tree density and canopy cover, from closed (high canopy cover) to open savannas (low canopy cover), and are located along shallow topographic gradients. We measured community-wide seedling limitation (i.e. proportion of 1-m 2 plots without seedlings of any woody species), photosynthetic photon flux density, litter cover, soil moisture and soil nutrients in each savanna type. Because closed savannas had lower PPFD and higher leaf litter cover than open savannas, we evaluated the effects of light level and litter cover on seedling emergence of nine dominant savanna woody species under controlled conditions in a glasshouse. Density, recruitment and survival of seedlings decreased over time because of mortality in all savanna types, but they were consistently higher in closed than in open savannas. Community-wide seedling limitation was significantly lower in closed (0.16 ± 0.03) than in open (0.30 ± 0.05) savannas. In the glasshouse, high litter cover and very low light levels reduced seedling emergence of most species, suggesting an adaptation to delay seed germination until the wet season when soil water availability is high and leaf litter rapidly decomposes. Synthesis: In Neotropical savannas, tree canopy cover facilitates seedling establishment of woody species by reducing stressful environmental conditions. In particular, low irradiance and high litter cover in closed savannas enhance the recruitment and survival of woody seedlings relative to open savannas by reducing soil water deficits and increasing nutrient availability in the upper soil layers. The higher seedling limitation of tree species in open than in closed savannas contributes to maintain relatively different balances between trees and herbaceous plants along topographic gradients in Neotropical savannas and helps to explain spatial distribution patterns of woody species in these ecosystems.